An e-REAL Lab in Dubai. Immersive Experiences, Visual Communication and Augmented Reality - Salvetti, Fernando; Bertagni, Barbara (International Journal of Advanced Corporate Learning (iJAC), 2015)
e-REAL is an enhanced reality lab by LKN and is at the forefront by design for learners’ centricity. It is becoming a cornerstone as a suite of solutions based on immersive experiences, visual communication and augmented reality. e-REAL is both a physical and a virtual ecosystem for boosting people and fostering their competencies: it embeds augmented reality tools, mobile applications, holograms and wearable devices to be used during education and training programs, as well as being utilized for assessment and development centers. e-REAL can be delivered both face to face and remotely. By implementing e-REAL, a myriad of competencies are fostered and audited: this includes behavioral skills, as well as cognitive and metacognitive capacity. Technical know-how and job-related competencies are also honed and attested. As a result, people’s performance is expected to grow; measuring return on investment and the outputs in terms of competencies’ growth is an easy task; the most demanding traceability standards are guaranteed.